2006
DOI: 10.1111/j.1834-7819.2006.tb00401.x
|View full text |Cite
|
Sign up to set email alerts
|

Flexural properties of glass fibre reinforced acrylic resin polymers

Abstract: Background: In recent years, glass fibres have been used to strengthen denture base resins. A major difficulty in using reinforcing fibres with multiphase acrylic resins, such as powder liquid resins, is inadequate impregnation of the fibres with the resin. Methods: This investigation examined the reinforcing effect of glass fibres on the fracture resistance and flexural strength of acrylic denture base resins. Eighty identical specimens were formed in specially designed moulds in accordance with the manufact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
1
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 22 publications
2
43
1
3
Order By: Relevance
“…This high amount of residual monomer (MELLO et al, 2003;. In tests evaluating resin cytotoxicity using denture bases of the material, it was found that the polymer and monomer proportion influences on the cytotoxicity of the final product (TACIR et al, 2006). However, nothing was mentioned about the mechanical characteristics of these materials, object of this study.…”
Section: Discussionmentioning
confidence: 87%
“…This high amount of residual monomer (MELLO et al, 2003;. In tests evaluating resin cytotoxicity using denture bases of the material, it was found that the polymer and monomer proportion influences on the cytotoxicity of the final product (TACIR et al, 2006). However, nothing was mentioned about the mechanical characteristics of these materials, object of this study.…”
Section: Discussionmentioning
confidence: 87%
“…There was evidence from dynamic in-vitro tests that glass fibre reinforcement increased fatigue resistance of dental appliance up to 100 times. 8 Various studies [2][3][4][5] have been described in the literature to discover the ideal material to reinforce provisional restorative materials. But none of these studies provide a conclusive idea about the material of choice.…”
Section: Discussionmentioning
confidence: 99%
“…There are several attempts [3][4][5][6][7][8][9][10][11][12][13][14][15][16] to increase the mechanical properties of denture base resins. One approach is to devise a reinforcement of denture base polymer with fibers, chips, or rods [12][13][14][15][16] . This technique is effective to improve the mechanical properties; however it is very difficult to incorporate accurately reinforcing materials in the desired position of the denture base resin.…”
Section: Discussionmentioning
confidence: 99%
“…Many attempts to improve the mechanical properties of polymethyl methacrylate (PMMA) have included using alternate polymers such as polycarbonate 3) , nylon 4,5) , copolymers 6,7) and urethane dimethacrylate (UDMA) 8,9) , and incorporating of butadiene-styrene rubber into PMMA matrix 10,11) . As another attempt, various fiber or chip materials [12][13][14][15][16] such as carbon, aramid and glass have been added into PMMA resin for reinforcing materials, and metal wires and meshes have ordinary been used for reinforcing materials to prevent the midline fracture of denture.…”
Section: Clinical Reportsmentioning
confidence: 99%